MUTYH Actively Contributes to Microglial Activation and Impaired Neurogenesis in the Pathogenesis of Alzheimer's Disease. (21st December 2021) - Mizuno, Yuri; Abolhassani, Nona; Mazzei, Guianfranco; Sakumi, Kunihiko; Saito, Takashi; Saido, Takaomi C.; Ninomiya, Toshiharu; Iwaki, Toru; Yamasaki, Ryo; Kira, Jun-ichi; Nakabeppu, Yusaku
Abstract : Oxidative stress is a major risk factor for Alzheimer's disease (AD), which is characterized by brain atrophy, amyloid plaques, neurofibrillary tangles, and loss of neurons. 8-Oxoguanine, a major oxidatively generated nucleobase highly accumulated in the AD brain, is known to cause neurodegeneration. In mammalian cells, several enzymes play essential roles in minimizing the 8-oxoguanine accumulation in DNA. MUTYH with adenine DNA glycosylase activity excises adenine inserted opposite 8-oxoguanine in DNA. MUTYH is reported to actively contribute to the neurodegenerative process in Parkinson and Huntington diseases and some mouse models of neurodegenerative diseases by accelerating neuronal dysfunction and microgliosis under oxidative conditions; however, whether or not MUTYH is involved in AD pathogenesis remains unclear. In the present study, we examined the contribution of MUTYH to the AD pathogenesis. Using postmortem human brains, we showed that various types of MUTYH transcripts and proteins are expressed in most hippocampal neurons and glia in both non-AD and AD brains. We further introduced MUTYH deficiency into App NL-G-F/NL-G-F knock-in AD model mice, which produce humanized toxic amyloid- β without the overexpression of APP protein, and investigated the effects of MUTYH deficiency on the behavior, pathology, gene expression, and neurogenesis. MUTYH deficiency improved memory impairment in App NL-G-F/NL-G-F mice, accompanied by reduced microgliosis. Gene expression profiling strongly suggested that MUTYH is involved in the microglial response pathways under AD pathology and contributes to the phagocytic activity of disease-associated microglia. We also found that MUTYH deficiency ameliorates impaired neurogenesis in the hippocampus, thus improving memory impairment. In conclusion, we propose that MUTYH, which is expressed in the hippocampus of AD patients as well as non-AD subjects, actively contributes to memory impairment by inducing microgliosis with poor neurogenesis in the preclinical AD phase and that MUTYH is a novel therapeutic target for AD, as its deficiency is highly beneficial for ameliorating AD pathogenesis.